Implementation of Progressive Islamic Policy in Regional Leaders of Muhammadiyah North Sumatra Period 2015 – 2020 - Yakub, M.; Sampurna, Ahmad (Nurani, 2023)
This research wants to find out the Implementation of Progressive Islamic Policy in the North Sumatra Muhammadiyah Regional Leaders for the 2015 – 2020 period, the supporting factors and obstacles encountered. Using the theory of policy implementation by George C. Edwards III, Merilee S. Grindle and David L. Weimer and Aidan R. Vining, to find out how intense implementation is in the North Sumatra PWM environment. At the same time solving the main problems in this study that are proposed in the problem formulation. Using historical methods with a qualitative approach. The results of the study answer the formulation of the problem, namely PWM North Sumatra has implemented Progressive Islamic movements in various fields (education, health, social, da'wah, humanity and nationality). The PWM program is in accordance with the policy of the central leadership implemented by the Muhammadiyah leadership of North Sumatra. PWM in implementing Progressive Islam faces various challenges both internal and external. Internally there are still many cadres who have not implemented the concept of Progressive Islam and other challenges. While externally there is a misunderstanding of the community towards PWM in terms of the purification of worship. And these challenges continue to be faced with preaching, education and providing good understanding to the community.